Percutaneous Cannulation for Extracorporeal Life Support in Severely and Morbidly Obese Patients. (September 2020) - Keyser, Andreas; Philipp, Alois; Zeman, Florian; Lubnow, Matthias; Lunz, Dirk; Zimmermann, Markus; Schmid, Christof
Background: Extracorporeal life support systems are well-established devices for treating patients with acute cardiopulmonary failure. Severe or morbid obesity may result in complications such as limb ischemia, bleeding, unsuccessful cannulation, or infection at the cannulation sites. This article reports on our experience with cannulation and associated complications in severely and morbidly obese patients. Methods: Between January 2006 and September 2016, 153 severely or morbidly obese patients with a body mass index >35 kg/m 2 were cannulated percutaneously for extracorporeal life support at our center. Among those, 115 patients were treated with venovenous extracorporeal membrane oxygenation (VV ECMO) for acute lung failure and 38 patients with venoarterial extracorporeal membrane oxygenation (VA ECMO) for cardiogenic shock. Complications related to percutaneous access and long-term follow-up were analyzed retrospectively. Primary focus was on the success of cannulation, outcome, thrombosis, bleeding, limb ischemia, and infection at the cannulation site. Normal-weight patients receiving extracorporeal life support served as control. Results: Percutaneous cannulation was successfully performed in all patients. Eighty-five (74%) patients were weaned from VV ECMO and 20 (52%) patients were weaned from VA ECMO. Limb ischemia requiring surgical intervention occurred in 5 (3%) patients, bleeding in 7 (5%) patients, and wound infection in 3 (2%) patients. In all other patients, decannulation was uneventful. These data as well as the long-term survival rates were comparable to those of normal-weight patients ( P > .05). Conclusion: Percutaneous vessel cannulation for extracorporeal life support systems is generally feasible. Therefore, percutaneous cannulation may well be performed in severely and morbidly obese patients. Patient outcome rather depends on appropriate support than on anatomy.